Sehen im Vergleich Transformationen von Blicken in der persischen und westeuropäischen Buchmalerei - Beyer, Vera (Reimer Verlag, 2020)
Vera Beyer compares transformations of gazes and gaze dispositives in Persian and Western European book illumination from the 13th to the 16th century. How are covetous gazes legitimized? What are the conditions of the gaze of God? When is pictorial contemplation idolatry? Topoi that circulate in both image cultures are questioned: Glimpses of the beauty of the Old Testament Joseph, the curtain before the throne of God, the portrait of Alexander the Great, dreaming authors, and unbelieving idolaters. The transformations of these topoi counter universalizations as well as essentializations, such as an image-hostile Islam versus an image-friendly Christianity. By combining transcultural art history and image studies, the book thus tests a transcultural critique of the gaze.